Dimensional Stability and Retention Strength of Impressions to Custom Impression Trays Fabricated Using Conventional Method and Additive Technology - An In-vitro Study - K Sangeetha Priyadarshini; V Vidyashree Nandini; Russia Marimuthu; Jailance Lathief (Indian Journal of Dental Research)
Background: 3D printing technology is replacing manual fabrication in all fields. 3D-printed impression trays should be assessed as they could replace conventional impression trays in the future. Aim: In-vitro comparison and evaluation of the dimensional stability and retention strength of impressions to custom impression trays fabricated using conventional method and additive technology. Materials and Methods: A maxillary edentulous auto-polymerizing acrylic resin model served as the master model. Two moulds were prepared from the master model in order to obtain 12 casts. One cast was scanned for 3D printing digital light processing (DLP) and fused deposition modelling (FDM) 24 impression trays using polylactic acid (PLA). Twelve casts were used to fabricate light cure impression trays. Polyvinyl-siloxane impressions were made on the master model using 36 impression trays and 18 trays each were used to assess dimensional stability and retention strength. Results: In dimensional stability analysis, one sample t-test revealed a statistically significant difference between each group and the master model followed by a one-way ANOVA. There were significant differences, but the difference was less with FDM trays (P < 0.05). In retention strength analysis, one-way Analysis of variance (ANOVA) revealed statistically significant difference between each group and post-hoc test revealed specific difference, the highest with FDM trays (P < 0.05). Conclusion: Dimensional changes were observed at 30 minutes and 72 hours. Lesser dimensional changes were observed when impressions were made using FDM trays followed by DLP and light cure trays. The mean retention strength seen in descending order was FDM, followed by DLP and light cure trays. The best retention strength was noticed when impressions were made using FDM trays.